An emerging consensus in palaeoanthropology: demography was the main factor responsible for the disappearance of Neanderthals - Krist Vaesen (Nature Portfolio, 2021)
Abstract The causes of Neanderthal disappearance about 40,000 years ago remain highly contested. Over a dozen serious hypotheses are currently endorsed to explain this enigmatic event. Given the relatively large number of contending explanations and the relatively large number of participants in the debate, it is unclear how strongly each contender is supported by the research community. What does the community actually believe about the demise of Neanderthals? To address this question, we conducted a survey among practicing palaeo-anthropologists (total number of respondents = 216). It appears that received wisdom is that demography was the principal cause of the demise of Neanderthals. In contrast, there is no received wisdom about the role that environmental factors and competition with modern humans played in the extinction process; the research community is deeply divided about these issues. Finally, we tested the hypothesis that palaeo-anthropologists’ stand in the debate co-varies with their socio-political views and attitudes. We found no evidence for such a correlation.